THE INFLUENCE OF CURRENT RATIO AND DEBT TO EQUITY RATIO ON RETURN ON ASSETS AT PT HANJAYA MANDALA SAMPOERNA TBK FOR THE PERIOD 2013 - 2022 - Rizka Wahyuni Amelia; Dina Lestari (International Journal Multidisciplinary Science, 2024)
This study examines the influence of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT Hanjaya Mandala Sampoerna Tbk over the period from 2013 to 2022. Using a descriptive quantitative approach, the research aims to clarify the relationship between CR, DER, and ROA in evaluating the company’s financial health and profitability. The findings reveal that CR does not have a significant individual impact on ROA, indicating that the company’s short-term liquidity does not directly affect its asset profitability. Conversely, DER has a significant negative impact on ROA, suggesting that higher debt relative to equity reduces asset returns, primarily due to increased interest burden. Simultaneously, CR and DER together have a significant impact on ROA, highlighting the need for balanced management of liquidity and leverage to maximize profitability. This study provides insights for company management and investors in assessing the financial strategies related to liquidity and debt structure to improve asset returns.